HIV ribonuclease H: continuing the search for small molecule antagonists. Issue 1 (January 2009) - Wendeler, Michaela; Beilhartz, Greg L; Beutler, John A; Göötte, Matthias; Le Grice, Stuart FJ
Members of the ribonuclease H (RNase H) family of enzymes (EC 3.1.26.4), which are found in nearly all organisms, are endoribonucleases that specifically hydrolyze the phosphodiester bond of RNA in a RNA––DNA hybrid. In retroviruses such as HIV-1, the RNase H activity is part of reverse transcriptase, the enzyme that converts the viral ssRNA into dsDNA suitable for integration into the host cell genome. In HIV-1, RNase H plays an essential role in various stages of reverse transcription, and it has been known for 20 years that inhibiting RNase H activity renders HIV noninfectious. However, the development of potent and selective antagonists of HIV RNase H has made surprisingly slow progress, and so far no RNase H inhibitor is in clinical trial, rendering this enzyme an important, but as yet underexplored, drug target. The recently described crystal structure of human RNase H in complex with a RNA––DNA hybrid provides new insight into the mechanism of HIV RNase H activity, with the potential to unveil new niches for therapeutic intervention. The current status of RNase H screening efforts is reviewed here.